Julio Irazusta: treinta años de nacionalismo argentino de Noriko Mutsuki. Editorial Biblos, 2004, Buenos Aires, 238 pp. - Piñeiro, Elena T. (2005)
Fil: Piñeiro, Elena T. Pontificia Universidad Católica Argentina; Argentina